2017
DOI: 10.5210/fm.v22i4.6914
|View full text |Cite
|
Sign up to set email alerts
|

“The perfect guide in a crowded musical landscape:” Online music platforms and curatorship

Abstract: Curatorship or curation has become a widely used term in music industry and popular music discourse recently, used not only in a museum or exhibition context, but also in connection with music festivals, and increasingly, playlists and other functions related to online music platforms. Through a case study of 22tracks, an online, playlist-based music discovery service currently based in four European cities, I look at the role and position of the music curator, and provide a critical analysis of the dominant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Because of their scale, capital and vertically integrated systems, the labels also strongly influenced what music was produced, promoted and sold to consumers (Lange and Bu¨rkner, 2013;Hracs, 2012). As the supply of recorded music increased music journalists, radio DJs, and record store clerks also emerged as influential sources of information and advice for consumers (Barna, 2017;Lange, 2016).…”
Section: The Case Of Music and The Evolving Role Of Music Curatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of their scale, capital and vertically integrated systems, the labels also strongly influenced what music was produced, promoted and sold to consumers (Lange and Bu¨rkner, 2013;Hracs, 2012). As the supply of recorded music increased music journalists, radio DJs, and record store clerks also emerged as influential sources of information and advice for consumers (Barna, 2017;Lange, 2016).…”
Section: The Case Of Music and The Evolving Role Of Music Curatorsmentioning
confidence: 99%
“…On Spotify, for example, users, who have been enrolled into the curation process, have created over 1.5b playlists (Bhaskar, 2016). Yet, many consumers are also seeking advice from a range of curators including music writers, algorithms and radio DJs (Barna, 2017;Lange, 2016;Hracs and Jansson, 2017). Whilst selling recorded music used to generate the most value, curating recorded music has become a key source of distinction, value and loyalty for competing distribution channels including record shops and music streaming services.…”
Section: The Case Of Music and The Evolving Role Of Music Curatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, and through the creation of editorially-curated playlists and individual tracks, album and artist recommendations, music streaming platforms have extended this practice to their digital platforms to help users overcome choice overload. All of the leading music streaming firms provide some forms of curation, including editorially-curated and personalised playlists and recommendations, such as Spotify's 'New Music Friday' playlist and Apple Music's 'New Music Mix' (Barna 2017, Eriksson et al 2019, Eriksson 2020. Despite the long history of curation in the music marketplace, Drott (2018a) highlights that music streaming platforms have successfully recast abundance as a problem and fabricated a need for assistance for which they claim to be uniquely positioned to resolve.…”
Section: The Case Of Recorded Musicmentioning
confidence: 99%
“…The platform studies literature has identified the practice of curationthe strategic selection, presentation and arrangement of information, goods, services, and peopleas central to how digital platforms generate value for themselves and their multiple users (Van Dijck 2013, Morris and Powers 2015, Barna 2017, Srnicek 2017, Jansson and Hracs 2018, Prey 2018, Drott 2018a, Webster 2019b, Eriksson 2020. By deciding what is valuable or relevant to a given situation and what is not, Bhaskar (2016) asserts that curation is reducing complexity, saving time, reducing cognitive burdens, filtering for quality and overcoming 'choice overload,' a bi-product of having abundant access to goods and services in the platform economy.…”
Section: Introductionmentioning
confidence: 99%